EFEKTIVITAS TERAPI MUSIK ROHANI DALAM MENINGKATKAN KUALITAS TIDUR LANSIA - Lantong, Yona; Lamonge, Annastasia; Wetik, Syenshie (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2022)
Introduction: Disturbed sleep patterns in the elderly are often caused by a disease process or part of a process of change due to aging. Poor sleep quality can have an impact on the sleep quality of the elderly. Lack of sleep experienced by the elderly can have effects on the physical, cognitive and quality of life of the elderly. Music therapy is a non-pharmacological therapy that has a relaxing effect to improve sleep quality. Objective: To analyze the effectiveness of spiritual music therapy on the sleep quality of the elderly at the Bethania Lembean Nursing Home. Method: The design used is the Pre-Experiment with the Pretest-posttest (before-after) approach. 25 elderly participants with poor sleep quality were recruited using purposive sampling method. The Wilcoxon test was used to analyze differences in sleep quality before and after spiritual music therapy interventions were given. Result: The results of statistical tests showed that there was a significant difference in the quality of sleep before and after being given spiritual music therapy with a p value of 0.000 (p <0.05). Spiritual music has advantages in terms of tempo and melody, which are slow and relaxing. Apart from that, spiritual lyrics have the meaning of strengthening and calming. Both of these provide a relaxing effect so as to improve the quality of the elderly's sleep. Conclusions: Giving spiritual music therapy can improve the sleep quality of the elderly.